Perception of Artificial Intelligence in Spain - Irene Albarrán; José Manuel Molina; Covadonga Gijón (International Telecommunications Society (ITS), 2020)
The present paper analyses perception of AI of individuals in Spain and the factors associated with it. Data on 6,308 individuals from the Spanish survey (CIS, 2018) are used. The data include several measures of perception, innovation, place of residence (autonomous regions and province), gender, age, educational level, and other socioeconomic and technical variables. A binary logit regression model is formulated and estimated for the attitude towards robots and artificial intelligence and its possible determinants. The results indicate that people have a negative attitude if they are not interested in scientific discoveries and technological developments and if AI and robots are not helpful at work.
Keywords: C21; C25; D12; D83; L63; L86; L96; P36; 330; perception; innovation; artificial intelligence; survey data; binary logit